CONCEPTUALIZATION OF TRANSFORMATIVE RESISTANCE OF INFRASTRUCTURE IN NON-STATIONARY CONDITIONS OF THE ANTHROPOCENE - Komračević, Miodrag; Živanović, Cvijetin; Tomić, Boban (ACADEMIC REVIEW, 2024)
Along with the technological progress and the deeper entry into the new geological era called the "Anthropocene", numerous scientific findings, empirical and statistical research unequivocally show that the existing civil infrastructure, due to the extreme complexity, changeability, non-stationarity and volatility that characterizes the Anthropocene, has no capacity for flexible, adaptable and reliable provision of services in circumstances with rapid changes in demand for service provision conditions and changeable environmental ones in which they operate. Namely, the previous infrastructural adaptation to extreme weather conditions, and especially to climate changes, was techno centric and firmly based on robustness - i.e. the ability to prevent or minimize disruptions or dysfunction of the infrastructure system or its part based on a risk assessment that emphasizes, in the foreground, control, protection and strengthening of the designed performance. However, the new Anthropocene and climate risks currently faced by critical infrastructure are not exclusively technological, but represent complex, interconnected, social, ecological and technical systems (SETS). Therefore, the techno centric strategies in new circumstances have a limited range, and even in certain situations have a counter effect. Instead, infrastructure in recent conditions requires more flexible and agile approaches and strategies and a paradigm shift that focuses on infrastructure resilience instead of protection and risk assessment. In this context, transformative resilience appears, both in politics and in practice, as the most favorable solution that is dictated by these Anthropocene risks, on the one hand, and effective tools, instruments, means and recipes that have not yet been developed in terms of solving current and upcoming and escalating threats.